MECHANISM OF GENDER STABILITY - H. Jabbarova (Journal Park Publishing, 2023)
The essence of criteria of gender stability is analyzed in the article. The transformation of gender equality, its importance in the life of the society is expressed. The importance of equality is based on human adaptation to social life.
Keywords: gender, social relations, social adaptation, gender audit, feminist movement, gender mechanisms.